(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: Incidence of visual disorders in industrial workers may result in visual loss, anguish, reduced manpower, man hours and economic loss. Most of these hazards are preventable if adequate precautionary measures are taken. [8,11] Worker’s eyes may be exposed to a variety of dangerous agents depending on the type of industry which may constitute an occupational hazard. According to OSHA, personal protective equipment is devices design to protect workers’ eyes from severe work place injury or illness resulting from contact with metal splash, chemical splash, dust, flying particle or radiation. [14,16] So the aim of the study is to assess Ocular Health, Visual & Refractive status of the workers working in the metal machinery (small scale) industries. METHODS: A clinical examination of the workers was accompanied by detailed occupational history in the small scale & tiny sector metal machinery industries. Visual acuity was measured using Snellen’s chart for distance and N notation reading chart for near. Color vision testing was done with Pseudoisochromatic-Ishihara chart. Anterior segment of eye was examining with the help of torch light and SLE. Fundus evaluation was done with the help of direct ophthalmoscope. Objective & Subjective Refraction was performed using Retinoscope and trial case. Stereopsis was measured with the help of Titmus Fly test. RESULTS: Hundred and eighty small scale industry workers were screened. Among them, all were male with a mean age (45.5 ± 11.31 years). 74% showed Visual impairment. The most common visual disorders were uncorrected presbyopia 65% (117), uncorrected refractive error 59% (106) out of which 17% (30) were already use their own spectacle prescription remaining 42% (76) were prescribed new spectacle. Color vision defect was found in 2% (3). Out of hundred and eighty only 11% (19) of the workers were use protective eye wear, remaining 89% (161) of them were never use protective eye wears on daily basis. CONCLUSION:This study concluded that uncorrected refractive error and uncorrected presbyopia was high among workers as they are not aware about eye health and safety measures for the occupation. The use of safety eye devices is low among workers and recommends that process about awareness and implementation of ocular safety in these industries is established as occupational protective measures are important for metal machinery industrial workers who are at a high risk of eye injuries. It is recommended that, there is a need to review the design, and reinforce the strict implementation of occupational eye safety programs.